Core–shell noble-metal@zeolitic-imidazolate-framework nanocarriers with high cancer treatment efficiency in vitro. Issue 7 (31st January 2019) - He, Liangcan; Pang, Kanglei; Liu, Wenwen; Tian, Yue; Chang, Lin; Liu, Xu; Zhao, Meiting; Liu, Yong; Li, Yantao; Jiang, Xingyu; Song, Rui; Liu, Yaling
Abstract : Core–shell Au@zeolitic-imidazolate-framework nanocarriers with high drug-loading, controlled drug release properties, and high cancer treatment efficiency. Abstract : Core–shell Au@zeolitic-imidazolate-framework-8 (ZIF-8) nanostructures are reported as a nanocarrier with both a high drug payload and high cancer treatment efficiency in vitro . Impressively, when used as multifunctional drug delivery vehicles, such core–shell Au@ZIF-8 nanostructures not only exhibit light- and pH-controlled drug release properties, but also provide two synergetic therapeutic modes for cancer treatment, resulting in 98% cell-killing activity after 30 min light irradiation followed by 24 h incubation even though HeLa cells are treated only by Au@ZIF-8 nanostructures loaded with 10 μM doxorubicin hydrochloride. All these results demonstrate the promising applications of this type of core–shell nanostructure in biomedical fields.